Evaluation of the effects of acetyl tributyl citrate as bio‐based plasticizer on the physical, thermal, and dynamical mechanical properties of poly(vinyl chloride)/polymethyl methacrylate blends. (8th July 2018) - Aouachria, Kamira; Massardier, Valérie; Benaniba, Mohamed Tahar; Belhaneche‐Bensemra, Naima
Abstract : This article details our work in studying the plasticization of Poly(vinyl chloride) (PVC)/Polymethyl methacrylate (PMMA) blends with bio‐based acetyl tributyl citrate (ATBC) in place of conventional plasticizers such as di(2‐ethylhexyl) phthalate. PMMA was blended with PVC in various ratios from 0 to 100 wt% by melt compounding with or without the plasticizer ATBC. Both the glass transition temperatures of the blends (differential scanning calorimetry) and Tα (dynamic mechanical thermal analysis) are consistent with a miscibility of the components, and Fourier transforms infrared spectroscopy studies show that there are specific interactions in the PVC/PMMA blends favoring the miscibility. The thermal degradation of the blends was studied by thermogravimetric analysis that shows the thermal degradation of rigid and plasticized PVC/PMMA is a process composed of two‐steps and that PMMA exercises a stabilizing effect on the thermal degradation of PVC during the first step by decreasing the rate of dehydrochlorination. J. VINYL ADDIT. TECHNOL., 25:E73–E82, 2019. © 2018 Society of Plastics Engineers